Analysis of the Use of Accounting Information and Non-Accounting Information in Supporting the Decision-Making Process of Lending by PT Bank Suluto, Calaca Branch - Virginia Prisela Mantiri; Stanly W. Alexander; Syermi S.E. Mintalangi (Asian Journal of Applied Business and Management, 2023)
In minimizing the risk of non-performing loans, banks need to conduct credit analysis to assess a credit application that contains various information, namely accounting information and non-accounting information. SulutGo Bank, Calaca Branch. The method used in this study is a qualitative method that is descriptive and the data obtained through interviews and documentation. The results of the study show that (1) accounting information is taken into consideration in the credit decision-making process at PT. Bank SulutGo Calaca Branch which is based on the use of financial ratio analysis related to credit (2) Non-accounting information is taken into consideration in the credit decision-making process at PT. Bank SulutGo Calaca Branch which refers to the 5c principle.